The influence of physical activity on BMR - Sjodin, A. M.; Forslund, A. H.; Westerterp, K. R.; Andersson, A. B.; Forslund, J. M.; Hambraeus, L. M. (Medicine & Science in Sports & Exercise, 1996)
In addition to factors such as fat free mass, hormonal status, genetics and energy balance, previous physical activity has been shown to influence energy turnover during resting (RMR = resting metabolic rate) or basal conditions (BMR = basal metabolic rate). This article presents data on BMR from elite endurance athletes (4 female and 4 male), at least 39 h after their last training session, in comparison with sedentary nonathletic controls matched for sex and fat free mass (FFM). Comparisons with theoretical calculations of BMR were also made. The athletes were shown to have a significantly higher BMR than was expected from calculations based on body mass (16%, P < 0.05) or body composition (12%, P < 0.05). There were no corresponding differences found in the nonathletic control group. The athletes had a 13% higher (P < 0.001) BMR than controls if related to FFM and 16% (P = 0.001) if related to both FFM and fat mass (FM). The athletes were also found to have 10% lower R-values (P < 0.01) indicating higher fat oxidation. The conformity of these findings with the present literature and the possible mechanisms behind them as well as its influence on theoretical calculations of energy turnover (ET) based on activity factors expressed as multiples of RMR are further discussed.